Visual Voices: Emotional Storytelling and Engagement in Social Media Health Campaigns - Subiantoro, Anjar; Malizal, Zelynda Zeinab (Indonesian Scientific Publication, 2025)
This study examines whether testimonial content on Instagram enhances emotional engagement and strengthens anti-smoking attitudes among Indonesian adolescents. Using a mixed-method design, 100 university students aged 18–24 were exposed to three types of Instagram posts: testimonial visuals, infographics, and text-based messages. Engagement metrics (likes, comments, shares) and sentiment-coded user comments were analyzed through ANOVA and thematic analysis. Results showed that testimonial posts generated the highest interaction, with likes (80%), comments (10%), and shares (5%), nearly doubling engagement compared to infographics and text formats. Sentiment analysis revealed empathy (40%) and fear (25%) as dominant emotional responses, indicating that emotional resonance enhances message retention and peer interaction. These findings suggest that testimonial storytelling on Instagram is more effective than data-driven formats in fostering anti-smoking attitudes among youth. Campaign designers and policymakers should prioritize culturally grounded testimonial narratives to increase relatability, encourage reflection, and promote behavior change, while ensuring inclusivity and ethical implementation.